Gossip as News: On Modern U.S. Celebrity Culture and Journalism - Feeley, Kathleen A. (History compass, 2012)
Scholars over the last half-century have begun to explore how gossip - spoken, printed, broadcast, or blogged - can serve to challenge, support, and/or reflect social, cultural, and political norms and ideals. Of particular interest here is how gossip, as amplified by the 20th- and 21st-century mass media, has transformed journalistic practice and the nature of public life in the United States. In the last decade, scholarship on the history of U.S. celebrity gossip culture and journalism has come of age; the much-studied classical Hollywood era has come under closer scrutiny, while study of the pre- and post-classical Hollywood periods has emerged to enrich our understanding of the production, distribution, and consumption of such news. An interdisciplinary and transnational literature, this body of work challenges old binaries of ‘hard’ versus ‘soft’ news to consider instead the long-term impact of celebrity journalism on modern meanings of selfhood and nationhood. These contributions to U.S. cultural, social, journalism, women’s and gender, and media history explore what it means to be a celebrated figure in modern America and the ever-evolving media individuals, institutions, products, and practices that produce and manage celebrity. Work remains to be done to explore fully how U.S. legal and political change has effected the development of celebrity journalism; the racial, ethnic, and sexual politics of celebrity gossip also deserve more in-depth analysis. We also await more work on the challenges and changes (or not) in the production, distribution, and consumption of gossip in this age of New Media.